Psychometric Assessment of a Physician-Patient Communication Behaviors Scale: The Perspective of Adult HIV Patients in Kenya - Juddy Wachira; Susan Middlestadt; Michael Reece; Chao-Ying Joanne Peng; Paula Braitstein (AIDS Research and Treatment)
Introduction. There have been no scales specifically developed to assess physician-patient communication behaviors (PPCB) in the sub-Saharan population. Aim. We revised an existing PPCB scale and tested its psychometric properties for HIV patients in Kenya. Methods. 17 items (five-point scale) measuring PPCB were initially adopted from the Matched Pair Instrument (MPI). Between July and August 2011, we surveyed a convenient sample of 400 HIV adult patients, attending three Academic Model Providing Healthcare program (AMPATH) clinics in Eldoret, Kenya. Of these 400, eight also participated in cognitive interviews, and 200 were invited to return after one week for follow-up interviews; 134 (67%) returned and were interviewed. Construct and content validity were established using an exploratory factor analysis, bivariate analyses, internal consistency, test-retest reliability and cognitive interviews. Results. Construct and content validity supported a one-dimensional measure of 13 PPCB items. Items assessed physicians’ effort to promote a favorable atmosphere for interaction with HIV patients. Biases associated with encoding and comprehension of specific terms, such as “discussion, involvement or concerns,” were noted. Internal consistency (Cronbach’s alpha = .81) and one-week retest reliability scores (.82) supported the reliability of the 13-item scale. Discussion. The revised PPCB scale showed acceptable validity and reliability in Kenya.